Film-forming resin for gravure printing inorganic ink, inorganic ink, preparation method and application thereof in automotive interior PVC decorative film

By using an emulsifier with an amphiphilic block structure as a film-forming resin and pigment dispersant for inorganic ink, the problem of insufficient coloring power and color uniformity of inorganic ink is solved, and an inorganic ink with high adhesion and weather resistance is achieved. Gravure printing on automotive interior decorative film.

CN116693742BActive Publication Date: 2025-02-11HANGZHOU HIWETECH CHEM TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310394394.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-13
Publication Date
2025-02-11
Estimated Expiration
2043-04-13

AI Technical Summary

Technical Problem

The existing inorganic ink has low coloring power and poor color brightness. Since pigment dispersion and resin latex synthesis are two independent processes, it is difficult to accurately regulate the pigment surface and latex pellet surface at the molecular level, resulting in The film formation uniformity and density of the ink layer are insufficient.

Method used

The emulsifier with hydrophilic and lipophilic segments with amphiphilic blocks is used as the dispersant of film-forming resin and pigment particles. By covering the pigment surface during pigment dispersion and fusing with the resin latex surface during film-forming process , to ensure the full fusion of pigment particles and the film-forming resin, thereby improving the film-forming uniformity and density of the ink layer.

Benefits of technology

Through this technical method, the coloring power and color display effect of inorganic ink are significantly improved, making its adhesion close to the level of traditional organic ink, and far superior to organic ink in terms of weather resistance. It is suitable for high weather resistance gravures of automotive interior decorative films Printing field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116693742B_ABST
    Figure CN116693742B_ABST
Patent Text Reader

Abstract

The present invention adopts an emulsifier with a hydrophilic and lipophilic amphiphilic block structure to prepare a film resin, and disperses and refines an inorganic pigment, thereby ensuring full fusion of the pigment particles and the surface of the film-forming latex particles, which is beneficial to improving the film-forming uniformity and compactness of the ink layer, and effectively solves the problem that the existing inorganic ink has low tinting power and poor color vividness. The present invention also provides a gravure printing ink, which includes the aforementioned film-forming resin, and the ink has the advantages of fine particle size, low viscosity, thermal storage stability without precipitation, no stratification, and very little viscosity change, and also has good tinting power and color display effect. Its weather resistance in high and low temperature sun-resistant cycle test is far better than that of organic ink, and it is expected to be used as a gravure printing inorganic ink with high weather resistance in the field of automotive interior decorative film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a film-forming resin for gravure printing inorganic water-based ink and a preparation method of inorganic water-based ink, and can be applied to the gravure printing field of automobile interior decoration film PVC decorative film. Background Art

[0002] With the rapid development of my country's automobile industry, the demand for automotive interior decorative films continues to grow. In modern cars, glass windows are getting bigger and bigger. When driving or parked in the open air, the interior space of the car will be exposed to direct sunlight. In ordinary summer, when the temperature outside the car is only 23°C, the surface temperature inside the car may exceed 70°C. As the sun sets, the temperature inside the car drops, which will affect the relative humidity inside the car and generate moisture. Direct sunlight and the contrast of hot and cold cycles within a day will affect the weather resistance of the printed layer of the interior decorative film. In view of the requirements of our automotive industry to reduce production costs and increase the degree of localization, it is very necessary to carry out research on high weather resistance decorative film printing ink.

[0003] Organic pigments are commonly used in printing inks. Compared with inorganic pigments, organic pigments usually have higher tinting power, and their particles are easy to grind and disperse, and not easy to precipitate, but their weather resistance and heat resistance are poor. Inorganic pigments are better than organic pigments in terms of weather resistance, heat resistance, and solvent resistance, but inorganic pigments have lower tinting power and poorer color brightness. In addition, due to their large specific gravity, the dispersion stability of inorganic pigments has always been a difficulty in the industry.

[0004] In addition, water-based ink is an ink made of water, specific water-based polymer resin, pigment and necessary additives. Among them, water-based polymer resin is the most important component. It mainly plays the role of a binder in water-based ink, allowing the pigment to be evenly dispersed, giving the ink a certain fluidity, and providing adhesion to the substrate material, so that the ink can form a uniform ink layer after printing. At the same time, since resin is a major component of the water-based ink formula system, the degree of fusion between the resin and the pigment surface determines the uniformity of the ink layer film formation, thereby determining the color display effect of the ink layer. The properties of the resin itself, such as light resistance, also have an important impact on the water-based ink layer. Since the dispersion of existing pigments and the synthesis of resin latex particles are two independent processes, it is difficult for water-based ink manufacturers to accurately control the surface of the pigment and the surface of the latex particles at the molecular level. Therefore, the fusion (homogenization) of the resin latex particles and the pigment surface is another major research problem in the current industry. Summary of the invention

[0005] The purpose of the present invention is to address the deficiencies of the prior art, and to prepare a film-forming resin (hereinafter referred to as resin B) using an emulsifier having hydrophilic and lipophilic segments of amphiphilic blocks. At the same time, the emulsifier is also used as a dispersant for pigment particles, thereby ensuring full fusion of the pigment particles with the surface of the film-forming latex particles, which is beneficial to improving the film-forming uniformity and density of the ink layer, and solving the problem of low tinting power and poor color brightness of existing inorganic water-based inks. Specifically, the film-forming resin that can improve film-forming uniformity and density is prepared by the following method:

[0006] 5 parts by weight of an emulsifier having a block copolymer structure is dissolved in 100 parts by weight of pure water to form an aqueous phase, 0.2 parts by weight of sodium bicarbonate is added, and then an oil phase consisting of 14 parts by weight of methyl methacrylate and 2 parts by weight of n-butyl acrylate is poured into a reactor and stirred and mixed at a speed of 200-300 rpm; the temperature of the reactor is raised to 75° C., stirring is maintained, nitrogen is passed through to deoxygenate for 10 minutes, 0.04 parts by weight of sodium persulfate is added, and the reaction is carried out for 1.5 hours until the monomer conversion rate reaches more than 95% by sampling and analysis; 28 parts by weight of n-butyl acrylate and 2 parts by weight of methyl methacrylate are added, and the reaction is continued for 2 hours until the monomer conversion rate reaches more than 95% by sampling and analysis; 0.08 parts by weight of a monomer is added An initiator aqueous solution prepared by dissolving 100 parts by weight of sodium persulfate in 4 parts by weight of pure water is added, and an oil phase monomer consisting of 12 parts by weight of methyl methacrylate and 1 part by weight of n-butyl acrylate is added, and the reaction is continued for 2-3 hours until the monomer conversion rate reaches more than 95% after sampling and analysis; an aqueous solution of tert-butyl hydroperoxide is added, the aqueous solution of tert-butyl hydroperoxide is obtained by dissolving 0.06 parts by weight of tert-butyl hydroperoxide in 0.6 parts by weight of pure water, and the mixture is stirred at a temperature of 10-20 minutes, and then an aqueous solution of rongalite is added, the aqueous solution of rongalite is obtained by dissolving 0.06 parts by weight of rongalite in 0.6 parts by weight of pure water, and the mixture is stirred at a temperature of 10-20 minutes, and then cooled to room temperature, and finally the material is filtered to obtain the resin B.

[0007] In the synthesis process of the resin B of the present invention, a block copolymer dispersant with water-oil amphiphilic chain segments used in the ink preparation process is used as an emulsifier. The dispersant (emulsifier) ​​is coated on the pigment surface during the pigment dispersion process. The resin B is used as a film-forming resin, and the surface of its latex particles is also covered with a consistent dispersant / emulsifier. This ensures that the pigment particles and the film-forming resin B are fully integrated during the film formation process of the water-based ink, which is beneficial to improving the film formation uniformity and density of the ink layer, thereby improving the tinting power and color display effect of the ink layer.

[0008] The aforementioned emulsifier has amphiphilic hydrophilic and lipophilic segments, and can be used as a macromolecular emulsifier for emulsion polymerization, and can also be used as a dispersant for dispersing and stabilizing inorganic pigments. Specifically, the chemical structure is:

[0009]

[0010] Wherein, n1 is the degree of polymerization of the methyl methacrylate monomer unit, n1=3-5; n2 is the methacrylic acid monomer unit, n2=22-30. In some preferred embodiments of the present invention, n1=4, n2=24.

[0011] The above emulsifier / dispersant uses polymethacrylic acid segments as hydrophilic segments, which has significant advantages over using polyacrylic acid segments or polyitaconic acid segments. Although they are both hydrophilic segments, the length of polyacrylic acid segments or polyitaconic acid segments is uncontrollable, which determines that they cannot be used as amphiphilic dispersants or emulsifiers. If the two polymerization degrees n1 and n2 are uncontrollable, amphiphilic products cannot be obtained.

[0012] The preparation method of the above emulsifier at least comprises:

[0013] (1) 3 g of the precursor, 0.2 g of azobisisocyanovaleric acid initiator, 37.84-51.6 g of M AA, and 106 g of dioxane were mixed, and after nitrogen was passed through to remove oxygen, the mixture was reacted at 80° C. for 2 hours;

[0014] The structural formula of the precursor is:

[0015] Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0016] The preparation of the precursor is prior art, including but not limited to references FERGUSON CJ, HUGHES RJ, NGUYEN D, PHAM BTT, GILBERT RG, SERELIS AK, SUCH CH, HAWKETT BS. Ab initioemulsion polymerization by RAFT-controlled self-assembly [J]. Macromolecules, 2005, 38 (6): 2191-2204.

[0017] (2) Add 6-10 g of MMA, 0.2 g of azobisisocyanovaleric acid initiator, and 32 g of dioxane, and react at 80° C. for 12 hours after nitrogen is passed through the mixture to remove oxygen;

[0018] (3) cooling to room temperature, using cyclohexane as a precipitant to precipitate the dispersant, and vacuum drying to obtain the emulsifier having a block copolymer structure.

[0019] In the present invention, the synthesis of the emulsifier adopts RAFT polymerization technology, and its product structure can be determined without doubt, and the structural formula can be verified by molecular weight characterization. RAFT technology can very effectively control the polymerization of monomers through the reversible degeneration transfer of growing free radicals, and realize the controllable regulation of polymer microstructure (such as synthetic block copolymers, etc.) and polymerization degree. It can be applied to the homopolymerization and copolymerization system of various monomers, and is applicable to almost all vinyl monomers, and the reaction conditions are no different from traditional free radical polymerization, and are applicable to various reaction systems such as bulk polymerization, solution polymerization, emulsion polymerization, and suspension polymerization. The present invention adopts the method of RAFT solution polymerization, and the proportion control of each component in the monomer addition order and the synthesis formula is obtained to obtain a dispersant with different polymerization degree and polymerization structure. Specifically, block copolymers can be regulated by monomer segmented feeding, and random copolymers can be regulated by mixing monomers once.

[0020] The present invention also provides an inorganic ink for gravure printing, which not only uses the aforementioned dispersant as an emulsifier to prepare a film-forming resin as the main component of the inorganic ink, but also uses the aforementioned dispersant to disperse and stabilize the inorganic pigment, thereby further improving the dispersion effect on the basis of ensuring full fusion between the pigment particles and the surface of the film-forming latex particles.

[0021] Compared with the "single-point adsorption" of conventional small molecule dispersants, the long-chain hydrophilic segments of the block structure dispersant of the present invention are dissolved in water after being neutralized and ionized by alkali solution (this type of dispersant with an amphiphilic block structure forms a "comb" structure in the water dispersion system, and the hydrophilic segments stretch toward the water phase and dissolve in water), which can greatly increase the thickness of the double electric layer of the pigment particles, thereby being more conducive to ensuring the dispersion stability of the pigment particles. On the other hand, under the same monomer composition conditions, the dispersant with a random copolymer structure only adopts a random copolymerization method, and ionizes the carboxylic acid groups on MAA by neutralizing and ionizing with alkali solution. The dispersant is adsorbed and "collapsed" on the surface of the inorganic pigment in the form of a "linear" polymer, realizing a "multi-point adsorption" stabilization mechanism. Compared with the dispersant with a random copolymer structure, the dispersant with a block structure can greatly increase the thickness of the double electric layer of the pigment particles, thereby being more conducive to ensuring the dispersion stability of the pigment particles. The principle diagram is shown in Figure 5 (b) of the specification. Therefore, the present invention creatively uses a macromolecular dispersant whose main components are block copolymers of MMA and MAA to disperse inorganic pigments, which is essentially different from conventional small-molecule dispersants and random copolymer macromolecular dispersants.

[0022] The aforementioned random copolymer structure dispersant also uses MMA and MAA, and its general structure is as follows:

[0023]

[0024] Wherein, n1 is the degree of polymerization of the methyl methacrylate monomer unit, n1=3-5; n2 is the degree of polymerization of the methacrylic acid monomer unit, n2=22-30. The preparation process is as follows:

[0025] (1) 3 g of the precursor, 0.4 g of azobisisocyanovaleric acid initiator, 37.84-51.6 g of MAA, 6-10 g of MMA, and 138 g of dioxane were mixed, and the mixture was reacted at 80° C. for 12 hours after nitrogen was passed to remove oxygen;

[0026] The structural formula of the precursor is:

[0027] Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0028] (2) cooling to room temperature, using cyclohexane as a precipitant to precipitate the dispersant, and vacuum drying to obtain the dispersant having a random copolymer structure.

[0029] It should be noted that, as an isomer of the emulsifier of the present invention, the dispersant with the above-mentioned random copolymer structure cannot be used to synthesize the film-forming resin (resin B) of the present invention. When the above-mentioned random copolymer is used as an emulsifier to prepare the film-forming resin, the polymerization process becomes unstable and the target resin product cannot be obtained.

[0030] Specifically, the inorganic ink is composed of the following raw materials in the following weight ratio: 10 parts of pigment, 34-44 parts of resin, 0.01-0.03 parts of alkaline neutralizer, 2-3 parts of emulsifier (dispersant), 0.8-1.2 parts of wetting agent, 1-4 parts of cosolvent, 0.1-0.16 parts of defoamer, and 38.64-47.96 parts of purified water. Among them, 34-44 parts of resin are the aforementioned film-forming resin.

[0031] In some preferred embodiments of the present invention, 34-44 parts of the resin include not only the aforementioned film-forming resin (resin B) but also resin A, which is prepared by the following method:

[0032] (1) Add 4g of Emulsogen APS100, 1.1g of NE-10, and 3g of n-butyl acrylate monomer to 90g of pure water, stir at 800rpm and heat to 90°C, reduce the stirring speed to 300rpm, add 4g of potassium persulfate aqueous solution (0.3g of potassium persulfate dissolved in 4g of pure water), and after the reaction system emits blue light, add 62g of n-butyl acrylate monomer and 12g of potassium persulfate aqueous solution (2g of potassium persulfate dissolved in 10g of pure water) dropwise, and both are added dropwise at the same time, and the addition time is 7h; then reduce the temperature of the reaction system to 63°C, add 1.5g of isopropanol, and then simultaneously add 6g of n-butyl acrylate monomer, 18g of AC-76, 10g of methyl methacrylate monomer, 0.8g of isopropylbenzene hydroperoxide, 0.6g of N,N-dimethyltoluidine, and 2g of The monomer addition phase of NE-10 was stirred at a stirring speed of 250 rpm, and the addition time was controlled to be 2 hours. 6.4 g of sodium bicarbonate aqueous solution (0.4 g of sodium bicarbonate was dissolved in 6 g of pure water) was added. The dropping speed of the sodium bicarbonate aqueous solution was adjusted based on maintaining the pH value of the reaction system at 5.5-7.5. After the monomer addition phase and the sodium bicarbonate aqueous solution were added, the mixture was stirred at room temperature for 1.5 hours. 2.08 g of tert-butyl hydroperoxide aqueous solution (0.08 g of tert-butyl hydroperoxide was dissolved in 2 g of pure water) was added. The mixture was stirred at room temperature for 10 minutes. 2.08 g of Rongalite aqueous solution (0.08 g of Rongalite was dissolved in 2 g of pure water) was added. The mixture was stirred at room temperature for 10 minutes. Finally, the mixture was cooled to room temperature and discharged to obtain a silicone acrylic emulsion with a silicone monomer content of nearly 23%.

[0033] (2) Take 50 g of the above-mentioned silicone-acrylic emulsion and add it into a dispersion kettle. Start stirring. At a stirring speed of 200-300 rpm, add 30 g of sodium silicate and 50 parts of silicon dioxide dispersion (silicon dioxide dispersion with a solid content of 30%-50% and a particle size of ≤100 nm). Keep stirring for 0.5-1 h and then filter the material to obtain the resin A.

[0034] In some preferred embodiments of the present invention, the resin A and the resin B are mixed in a mass ratio of 20-28:14-16 to form the resin. The present invention uses the inorganic system-based resin A and the organic polymer emulsion resin B as the composite resin of the system. The resin A can greatly improve the rigidity and weather resistance of the coating, while the resin B mainly plays the role of assisting the bonding of the pigment. The combined use can improve the flexibility of the ink layer; in addition, the resin A participates in the grinding of the inorganic ink paste, plays an auxiliary role in the dispersion and stabilization of the inorganic pigment, and forms a synergistic effect with the dispersant.

[0035] In the present invention, the inorganic pigments include but are not limited to: inorganic iron red pigment, iron oxide yellow, iron oxide blue, and inorganic carbon black.

[0036] The present invention also provides a method for preparing the aforementioned inorganic ink, comprising: adding 22-28 parts by weight of resin A into a dispersion kettle, starting stirring, maintaining the rotation speed at 100-200 rpm, then sequentially adding 10-14 parts by weight of pure water, 0.01-0.03 parts by weight of an alkaline neutralizer, 2-3 parts by weight of a dispersant, 0.04-0.06 parts by weight of a defoamer and 10 parts by weight of a pigment, stirring and mixing at a rate of 200-500 rpm until uniform, and then transferring to a horizontal sand mill for grinding. After the color paste particle size reaches below 300nm, the material is filtered out to obtain a water-based color paste; then the obtained water-based color paste, 14-16 parts by weight of resin B, 24.64-37.9 parts by weight of pure water remaining in the formula, 1-1.2 parts by weight of a wetting agent, 1-4 parts by weight of a co-solvent and 0.06-0.1 parts by weight of a defoaming agent are sequentially added into a dispersion tank, stirred at a rate of 150-250rpm for 0.5-1h, and then filtered out to obtain the highly weather-resistant gravure printing inorganic ink.

[0037] Compared with the prior art, the beneficial effects of the present invention are: the inorganic water-based ink prepared by the present invention has fine particle size, low viscosity, good storage stability, adhesion and tinting strength on the substrate are close to the level of traditional organic water-based ink, and weather resistance is far superior to organic water-based ink. It is expected to be used as a highly weather-resistant gravure printing inorganic water-based ink in the field of automotive interior decorative films. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a printing effect diagram of Example 5 of the present invention, in which the inorganic red ink is printed on the PVC automobile decorative inner film by a KPP gravure proofing machine.

[0039] Figure 2 This is a printing effect diagram of Example 9 of the present invention, in which the inorganic yellow ink is printed on the PVC automobile decorative inner film by a KPP gravure proofing machine.

[0040] Figure 3 This is a printing effect diagram of Example 11 of the present invention, in which inorganic blue ink is printed on a PVC automobile decorative inner film by a KPP gravure proofing machine.

[0041] Figure 4 This is a printing effect diagram of Example 13 of the present invention, in which the inorganic black ink is printed on the PVC automobile decorative inner film by a KPP gravure proofing machine.

[0042] Figure 5(a) is a schematic diagram of the “multi-point adsorption” stabilization mechanism, and Figure 5(b) is a schematic diagram of the block “comb” type stabilization mechanism. DETAILED DESCRIPTION

[0043] In the present invention, the silicon dioxide dispersion, wetting agent, cosolvent, foaming agent and purified water are all commercially available products.

[0044] The silica dispersion has a solid content of 30%-50% and a particle size of ≤100 nm (such as R301, AkzoNoble; R302, AkzoNoble; R303, AkzoNoble; R402, AkzoNoble; R1050, AkzoNoble; R1020, AkzoNoble; R1010, AkzoNoble; R900, AkzoNoble; WV33, AkzoNoble; XP4080, AkzoNoble), with R1020 (AkzoNoble) being particularly preferred.

[0045] The alkaline neutralizer may be any one of sodium hydroxide, potassium hydroxide, monoethanolamine, diethanolamine, and triethanolamine, and monoethanolamine is particularly preferred.

[0046] The wetting agent is a fluorinated modified polyacrylate wetting agent (such as LeAD177, produced by Lijia Additive Co., Ltd.), a polyether siloxane wetting agent (such as BYK-345, BYK-346, BYK-347, BYK-349, produced by BYK Company), or a mixture of any proportion of two or more thereof, preferably a polyether siloxane wetting agent, and particularly preferably BYK-349 (BYK Company).

[0047] The co-solvent can be one of ethanol, isopropanol, and n-propanol, or a mixture of two or more of them in any proportion, preferably ethanol (Suzhou Oute Chemical Co., Ltd.).

[0048] The defoamer of the present invention is a low-grade alcohol defoamer (such as DAPPO R DF 3163, Deqian Company), mineral oil defoamers (such as Defom R W-074, Defom R W-082, Defom R W-098, Deqian Company; ADVANTAGE AM-1512, ASHLAND-AQUALON Company), silicone defoamers (such as G308, Milliken Chemical Group Co., Ltd., USA) or a mixture of any two or more in any proportion, preferably low-grade alcohol defoamers, especially DAPPO R DF 3163 (Deqian Company).

[0049] The purified water refers to tap water purified by a LRO PVC primary reverse osmosis pure water device (Shanghai Sina Light Industry Machinery Equipment Co., Ltd.) to a conductivity of no more than 50 us / cm (25° C.).

[0050] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0051] In the following examples, the precursors were prepared by the method described in Ferguson CJ, Hughes RJ, Nguyen D, Pham B TT, Gilbert RG, Serelis AK, Such CH, Hawkett B S. Ab initio emulsion polymerization by RAFT-controlled self-assembly [J]. Macromolecules, 2005, 38 (6): 2191-2204. The product was measured by the test method described in the literature to have the structural formula: Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0052] In the following examples, the preparation method of resin A is as follows:

[0053] (1) 4 g of Emulsogen APS100 (Kline), 1.1 g of 1.5 parts by weight of NE-10 (ADEKA), and 3 g of n-butyl acrylate (Shanghai Hechuang Chemical Technology Co., Ltd.) monomer were added to 90 g of pure water, stirred at a stirring speed of 800 rpm and heated to 90° C., then the stirring speed was reduced to 300 rpm, and 4 g of potassium persulfate (Suzhou Huahang Chemical Technology Co., Ltd.) aqueous solution (0.3 g of potassium persulfate was dissolved in 4 g of pure water) was added. After the reaction system showed obvious blue light, 62 g of n-butyl acrylate monomer (Shanghai Hechuang Chemical Technology Co., Ltd.) and 12 g of potassium persulfate aqueous solution (Suzhou Huahang Chemical Technology Co., Ltd.) (2 g of potassium persulfate was dissolved in 10 g of pure water) were added dropwise at the same time. The two were added dropwise at the same time. The addition time was 7 hours. Then the temperature of the reaction system was reduced to 63° C., 1.5 g of isopropanol (Yonghua Chemical Technology (Jiangsu) Co., Ltd.) was added, and then 6 g of n-butyl acrylate monomer (Shanghai Hechuang Chemical Technology Co., Ltd.), 18 g of AC-76 (Fangzhou (Fogang) Chemical Materials Co., Ltd.), 10g methyl methacrylate monomer (Shanghai Hechuang Chemical Technology Co., Ltd.), 0.8g cumene hydroperoxide (SIGMA-ALDRICH), 0.6g N,N-dimethyltoluidine (Tianjin CITIC Kaitai Chemical Co., Ltd.), 2g NE-10 (ADEKA) was stirred at a stirring speed of 250 rpm for the mixed monomer addition phase, and the addition time was controlled to be 2 h. 6.4 g of sodium bicarbonate aqueous solution (Suzhou Huahang Chemical Technology Co., Ltd.) was added (0.4 g of sodium bicarbonate was dissolved in 6 g of pure water). The dropping speed of the sodium bicarbonate aqueous solution was adjusted to maintain the pH value of the reaction system at 5.5-7.5. The pH value of the reaction system was measured every 20 min. After the monomer addition phase and the sodium bicarbonate aqueous solution were added, the mixture was stirred at room temperature for 1.5 h. 2.08 g of tert-butyl hydroperoxide (Shanghai Baiyi Chemical Co., Ltd.) aqueous solution (0.08 g of tert-butyl hydroperoxide was dissolved in 2 g of pure water) was added. The mixture was stirred at room temperature for 10 min. 2.08 g of Rongalite (Shanghai Fengrui Chemical Co., Ltd.) aqueous solution (0.08 g of Rongalite was dissolved in 2 g of pure water) was added. The mixture was stirred at room temperature for 10 min. Finally, the mixture was cooled to room temperature and discharged to obtain a silicone acrylic emulsion having a silicone monomer content of nearly 23%.

[0054] (2) Take 50 g of the above-mentioned silicone-acrylic emulsion and add it into a dispersion kettle. Start stirring. At a stirring speed of 200-300 rpm, add 30 g of sodium silicate (Jiangxi Yigao Chemical Industry Development Co., Ltd.) and 50 parts of silicon dioxide dispersion. Keep stirring for 0.5-1 h and then filter the material to obtain the resin A.

[0055] In the following examples, the preparation method of resin B is as follows:

[0056] (1) 5 parts by weight of a dispersant having a block copolymer structure (Examples 1-6, Examples 8, 13, and 14 use a dispersant having a block copolymer structure with n1=4 and n2=24 for the synthesis of resin B; Examples 9 and 10 use a dispersant having a block copolymer structure with n1=3 and n2=22 for the synthesis of resin B; Examples 11 and 12 use a dispersant having a block copolymer structure with n1=5 and n2=30 for the synthesis of resin B) are dissolved in 100 parts by weight of pure water to form an aqueous phase, 0.2 parts by weight of sodium bicarbonate (Suzhou Huahang Chemical Technology Co., Ltd.) is added, and then an oil phase consisting of 14 parts by weight of methyl methacrylate (Shanghai Hechuang Chemical Technology Co., Ltd.) and 2 parts by weight of n-butyl acrylate (Shanghai Hechuang Chemical Technology Co., Ltd.) is poured into a reactor and stirred and mixed at a speed of 200-300 rpm.

[0057] (2) The temperature of the reactor was raised to 75° C., stirring was maintained, and nitrogen was passed through to deoxygenate for 10 minutes. 0.04 parts by weight of sodium persulfate (Suzhou Huahang Chemical Technology Co., Ltd.) was added, and the reaction was continued for 1.5 hours until the monomer conversion rate reached 95% or more by sampling and analysis; 28 parts by weight of n-butyl acrylate (Shanghai Hechuang Chemical Technology Co., Ltd.) and 2 parts by weight of methyl methacrylate (Shanghai Hechuang Chemical Technology Co., Ltd.) were added to the oil phase monomer, and the reaction was continued for 2 hours until the monomer conversion rate reached 95% or more by sampling and analysis; an initiator aqueous solution prepared by dissolving 0.08 parts by weight of sodium persulfate (Suzhou Huahang Chemical Technology Co., Ltd.) in 4 parts by weight of pure water was added, and 12 parts by weight of methyl methacrylate (Shanghai Hechuang Chemical Technology Co., Ltd.) was added to the initiator aqueous solution; Technology Co., Ltd.), 1 part by weight of n-butyl acrylate (Shanghai Hechuang Chemical Technology Co., Ltd.), and continue to react for 2-3 hours until the monomer conversion rate reaches more than 95% when sampled and analyzed; add tert-butyl hydroperoxide aqueous solution, the tert-butyl hydroperoxide aqueous solution is obtained by dissolving 0.06 part by weight of tert-butyl hydroperoxide (Shanghai Baiyi Chemical Co., Ltd.) in 0.6 part by weight of pure water, keep warm and stir for 10-20 minutes, then add Rongalite aqueous solution, the Rongalite aqueous solution is obtained by dissolving 0.06 part by weight of Rongalite (Shanghai Fengrui Chemical Co., Ltd.) in 0.6 part by weight of pure water, keep warm and stir for 10-20 minutes, then cool to room temperature, and finally filter out the material to obtain the resin B.

[0058] The monomer conversion rate during the preparation of resin B was measured by gravimetric method.

[0059] The particle size test of resin A, resin B and ink paste was carried out on Malvern ZETASIZER 3000HAS particle size analyzer at a test temperature of 25°C.

[0060] The viscosity of the inorganic ink was measured on a BGD 152S smart touch viscometer.

[0061] The storage stability of inorganic ink means that the inorganic water-based ink can be left standing at 60°C for 9 days without precipitation or stratification, and the viscosity change before and after hot storage does not exceed 30%, which means that the storage stability of the inorganic water-based ink is >6 months.

[0062] The adhesion test of inorganic water-based ink is carried out according to GB / T 13217.7-2009. If the ink adhesion fastness is ≥95%, the ink adhesion fastness can be considered excellent.

[0063] The tinting strength of inorganic ink is tested in accordance with GB / T 13217.6-2008 “Test method for tinting strength of liquid ink”.

[0064] The weatherability test conditions of inorganic ink are as follows: the glass plate printed with inorganic ink is irradiated with UVA light source at 80℃ and 50% humidity for 12 hours, and then irradiated with UVA light source at 20℃ and 95% humidity for 12 hours. The above two steps are repeated until the total irradiation time reaches 300 hours. The color difference △E of the same area before and after the weatherability test is measured using X-Rite eXact portable spectrophotometer Lab If the naked eye observes the illuminated area before and after the test, there is no obvious fading, and △E Lab ≤2, it indicates that the ink has good weather resistance.

[0065] Table 1. Performance indicators of resin A and resin B

[0066] Resin A Resin B Particle size and particle size distribution 89.63nm, 0.234 156.76nm, 0.328 Monomer conversion - 95.34%,96.89%,98.45%

[0067] As can be seen from Table 1, in the polymerization of resin B carried out by using the dispersant having a block copolymer structure prepared by the present invention as an emulsifier, the monomer conversion rate of each step is close to complete, and the whole process is stable and controllable, which proves the feasibility of applying the dispersant in emulsion polymerization.

[0068] In the following examples, the molecular weight characterization of the dispersant was carried out on a gel permeation chromatograph Waters 1525-2414-717 GPC instrument, with tetrahydrofuran as the eluent and calibration using narrow distribution polystyrene standards.

[0069] Example 1 (conventional small molecule dispersant + resin B + inorganic pigment):

[0070] 32 parts of pure water, 2 parts of dispersant TEGO Dispers 740W (Evonik), 0.04 parts of DAPPO R DF 3163 (Deqian Company) and 10 copies 4130 (Lanxess) was added into the dispersion kettle, stirring was started, and the mixture was evenly stirred at a rate of 200 rpm, and then transferred to a horizontal sand mill. After grinding for 6 times, the material was filtered out to obtain an aqueous red slurry; then the aqueous red slurry, 16 parts of resin B, the remaining 37.9 parts of purified water in the formula, 1 part of BYK-349 (BYK), 1 part of ethanol (Suzhou Outer Chemical Co., Ltd.) and 0.06 parts of DAPPO were sequentially added. R DF 3163 (Deqian Company) was added into the dispersion tank, stirred at a rate of 150 rpm for 0.5 h, and then filtered to obtain inorganic red ink for gravure printing.

[0071] Embodiment 2 (resin A+inorganic pigment):

[0072] Add 22 parts of resin A to the dispersion kettle, start stirring, keep the speed at 100 rpm, then add 10 parts of pure water, 0.04 parts of DAPPO R DF 3163 (Deqian Company) and 10 copies 4130 (Lanxess), and stirred at a speed of 200 rpm to mix evenly, then transferred to a horizontal sand mill, ground for 8 times and filtered to obtain a water-based red slurry; then the obtained water-based red slurry, 16 parts of resin B, the remaining 37.9 parts of purified water in the formula, 1 part of BYK-349 (BYK), 1 part of ethanol (Suzhou Outer Chemical Co., Ltd.) and 0.06 parts of DAPPO R DF 3163 (Deqian Company) was added into the dispersion tank, stirred at a rate of 150 rpm for 0.5 h, and then filtered to obtain inorganic red ink for gravure printing.

[0073] Example 3 (dispersant with block copolymer structure + resin B + inorganic pigment):

[0074] Step 1: Preparation of dispersant:

[0075] (1) 3 g of the precursor, 0.2 g of azobisisocyanovaleric acid initiator, 41.28 g of MAA, and 106 g of dioxane were mixed, and after nitrogen was passed through to remove oxygen, the mixture was reacted at 80° C. for 2 hours. The structural formula of the precursor is: Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0076] (2) Add 8 g of MMA, 0.2 g of azobisisocyanovaleric acid initiator, and 32 g of dioxane, and react at 80° C. for 12 hours after nitrogen is passed through to remove oxygen;

[0077] (3) After cooling to room temperature, the dispersant was precipitated out using cyclohexane as a precipitant, and the product was dried in vacuo. The molecular weight characterization results were as follows:

[0078] Table 2 Molecular weight characterization results of block copolymer dispersants

[0079]

[0080] According to the GPC (gel permeation chromatography) test, the molecular weight increases gradually with the addition of MAA and MMA monomers. The measured molecular weight is basically consistent with the designed molecular weight, and the controllability is good. Its structural formula is:

[0081]

[0082] Among them, n1=4, n2=24.

[0083] Step 2: Preparation of ink:

[0084] 32 parts of purified water, 0.01 parts of monoethanolamine (BASF), 2 parts of the above block copolymer dispersant, 0.04 parts of DAPPO R DF 3163 (Deqian Company) and 10 copies 4130 (Lanxess) was added to the dispersion kettle, stirring was started, and the mixture was stirred at a rate of 200 rpm until uniform. After that, it was transferred to a horizontal sand mill, ground for 4 times, and then filtered to obtain an aqueous inorganic red slurry. Then, the aqueous red slurry, 16 parts of resin B, the remaining 37.9 parts of pure water in the formula, 1 part of BYK-349 (BYK), 1 part of ethanol (Suzhou Outer Chemical Co., Ltd.) and 0.06 parts of DAPPO were sequentially added. R DF3163 (Deqian Company) was added into the dispersion tank, stirred at a rate of 150 rpm for 0.5 h, and then filtered to obtain inorganic red ink for gravure printing.

[0085] Embodiment 4 (dispersant with random copolymer structure+resin B+inorganic pigment):

[0086] Step 1: Preparation of dispersant:

[0087] (1) 3 g of the precursor, 0.4 g of azobisisocyanovaleric acid initiator, 41.28 g of MAA, 8 g of MMA, and 138 g of dioxane were mixed, and the mixture was reacted at 80° C. for 12 hours after nitrogen was passed through the mixture to remove oxygen. The structural formula of the precursor is: Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0088] (2) After cooling to room temperature, the dispersant was precipitated using cyclohexane as a precipitant, and vacuum dried to obtain a dispersant with a random copolymer structure. The molecular weight characterization results are as follows:

[0089] Table 3. Random copolymer dispersant molecular weight characterization results

[0090]

[0091] According to the GPC (gel permeation chromatography) test, the molecular weight increases once the mixed monomers of MAA and MMA are added. The measured molecular weight is basically consistent with the designed molecular weight, and the controllability is good. The structural formula is as follows:

[0092]

[0093] Among them, n1=4, n2=24.

[0094] Step 2: Preparation of ink:

[0095] 32 parts of purified water, 0.01 parts of monoethanolamine (BASF), 2 parts of the above random copolymer dispersant, 0.04 parts of DAPPO R DF 3163 (Deqian Company) and 10 copies 4130 (Lanxess) was added to the dispersion kettle, stirring was started, and the mixture was stirred at a rate of 200 rpm until uniform. After that, it was transferred to a horizontal sand mill, ground for 4 times, and then filtered to obtain an aqueous inorganic red slurry. Then, the aqueous red slurry, 16 parts of resin B, the remaining 37.9 parts of pure water in the formula, 1 part of BYK-349 (BYK), 1 part of ethanol (Suzhou Outer Chemical Co., Ltd.) and 0.06 parts of DAPPO were sequentially added. R DF3163 (Deqian Company) was added into the dispersion tank, stirred at a rate of 150 rpm for 0.5 h, and then filtered to obtain inorganic red ink for gravure printing.

[0096] Embodiment 5 (dispersant with block copolymer structure + resin A + resin B + inorganic pigment):

[0097] Step 1: Preparation of dispersant:

[0098] (1) 3 g of the precursor, 0.2 g of azobisisocyanovaleric acid initiator, 41.28 g of MAA, and 106 g of dioxane were mixed, and after nitrogen was passed through to remove oxygen, the mixture was reacted at 80° C. for 2 hours. The structural formula of the precursor is: Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0099] (2) Add 8 g of MMA, 0.2 g of azobisisocyanovaleric acid initiator, and 32 g of dioxane, and react at 80° C. for 12 hours after nitrogen is passed through to remove oxygen;

[0100] (3) Cooling to room temperature, using cyclohexane as a precipitant to precipitate the dispersant, and vacuum drying to obtain the dispersant having a block copolymer structure with n1=4 and n2=24.

[0101] Step 2: Preparation of ink:

[0102] 22 parts of resin A were added to the dispersion kettle, stirring was started, and the speed was maintained at 100 rpm. Then 10 parts of purified water, 0.01 parts of monoethanolamine (BASF), 2 parts of the above block copolymer dispersant, 0.04 parts of DAPPO R DF3163 (Deqian Company) and 10 copies 4130 (Lanxess), and stirred and mixed at a speed of 200 rpm, and then transferred to a horizontal sand mill, ground until the color paste particle size reaches less than 200 nm, and then filtered to obtain an aqueous red paste; then the obtained aqueous red paste, 16 parts of resin B, the remaining 37.9 parts of purified water in the formula, 1 part of BYK-349 (BYK), 1 part of ethanol (Suzhou Out Chemical Co., Ltd.) and 0.06 parts of DAPPO R DF 3163 (Deqian Company) was added into the dispersion tank, stirred at a rate of 150 rpm for 0.5 h, and then filtered to obtain the highly weather-resistant inorganic red gravure ink.

[0103] Embodiment 6 (dispersant with random copolymer structure + resin A + resin B + inorganic pigment):

[0104] Step 1: Preparation of dispersant:

[0105] (1) 3 g of the precursor, 0.4 g of azobisisocyanovaleric acid initiator, 41.28 g of MAA, 8 g of MMA, and 138 g of dioxane were mixed, and the mixture was reacted at 80° C. for 12 hours after nitrogen was passed through the mixture to remove oxygen. The structural formula of the precursor is: Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0106] (2) Cooling to room temperature, using cyclohexane as a precipitant to precipitate the dispersant, and vacuum drying to obtain the dispersant having a random copolymer structure. Vacuum drying to obtain the dispersant having a random copolymer structure with n1=4 and n2=24.

[0107] Step 2: Preparation of ink:

[0108] 22 parts of resin A were added to the dispersion kettle, stirring was started, and the speed was maintained at 100 rpm. Then 10 parts of purified water, 0.01 parts of monoethanolamine (BASF), 2 parts of the above random copolymer dispersant, 0.04 parts of DF3163 (Deqian Company) and 10 copies 4130 (Lanxess), and stirred and mixed at a speed of 200 rpm, and then transferred to a horizontal sand mill, ground for 4 times and filtered to obtain a water-based red slurry; then the obtained water-based red slurry, 16 parts of resin B, the remaining 37.9 parts of purified water in the formula, 1 part of BYK-349 (BYK), 1 part of ethanol (Suzhou Outer Chemical Co., Ltd.) and 0.06 parts of DF 3163 (Deqian Company) was added into the dispersion tank, stirred at a rate of 150 rpm for 0.5 h, and then filtered to obtain the highly weather-resistant inorganic red gravure ink.

[0109] Example 7 (dispersant with block copolymer structure + resin A + conventional resin + inorganic pigment):

[0110] Step 1: Preparation of dispersant:

[0111] (1) 3 g of the precursor, 0.2 g of azobisisocyanovaleric acid initiator, 41.28 g of MAA, and 106 g of dioxane were mixed, and after nitrogen was passed through to remove oxygen, the mixture was reacted at 80° C. for 2 hours. The structural formula of the precursor is: Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0112] (2) Add 8 g of MMA, 0.2 g of azobisisocyanovaleric acid initiator, and 32 g of dioxane, and react at 80° C. for 12 hours after nitrogen is passed through to remove oxygen;

[0113] (3) Cooling to room temperature, using cyclohexane as a precipitant to precipitate the dispersant, and vacuum drying to obtain the dispersant having a block copolymer structure with n1=4 and n2=24.

[0114] Step 2: Preparation of ink:

[0115] 22 parts of resin A were added to the dispersion kettle, stirring was started, and the speed was maintained at 100 rpm. Then 10 parts of purified water, 0.01 parts of monoethanolamine (BASF), 2 parts of the above block copolymer dispersant, 0.04 parts of DAPPO R DF3163 (Deqian Company) and 10 copies 4130 (Lanxess), and stirred and mixed at a rate of 200 rpm, and then transferred to a horizontal sand mill, ground until the color paste particle size reached below 200 nm, and then filtered to obtain an aqueous red paste; then the obtained aqueous red paste, 16 parts of resin 7256 (BASF), the remaining 37.9 parts of purified water in the formula, 1 part of BYK-349 (BYK), 1 part of ethanol (Suzhou Out Chemical Co., Ltd.) and 0.06 parts of DAPPO RDF 3163 (Deqian Company) was added into the dispersion tank, stirred at a rate of 150 rpm for 0.5 h, and then filtered to obtain the highly weather-resistant inorganic red gravure ink.

[0116] Embodiment 8 (dispersant with block copolymer structure+resin A+resin B+organic pigment):

[0117] Step 1: Preparation of dispersant:

[0118] (1) 3 g of the precursor, 0.2 g of azobisisocyanovaleric acid initiator, 41.28 g of MAA, and 106 g of dioxane were mixed, and after nitrogen was passed through to remove oxygen, the mixture was reacted at 80° C. for 2 hours. The structural formula of the precursor is: Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0119] (2) Add 8 g of MMA, 0.2 g of azobisisocyanovaleric acid initiator, and 32 g of dioxane, and react at 80° C. for 12 hours after nitrogen is passed through to remove oxygen;

[0120] (3) Cooling to room temperature, using cyclohexane as a precipitant to precipitate the dispersant, and vacuum drying to obtain the dispersant having a block copolymer structure with n1=4 and n2=24.

[0121] Step 2: Preparation of ink:

[0122] 22 parts of resin A were added to the dispersion kettle, stirring was started, and the speed was maintained at 100 rpm. Then 10 parts of purified water, 0.01 parts of monoethanolamine (BASF), 2 parts of the above block copolymer dispersant, 0.04 parts of DAPPO R DF3163 (Deqian Company) and 10 parts of anthraquinone polycyclic ketone organic red 177 (PR177, Zhejiang Lily Group Co., Ltd.), and stirred and mixed at a rate of 200 rpm, and then transferred to a horizontal sand mill, ground until the color paste particle size reaches less than 200 nm, and then filtered to obtain an aqueous red paste; then the obtained aqueous red paste, 16 parts of resin B, the remaining 37.9 parts of pure water in the formula, 1 part of BYK-349 (BYK Company), 1 part of ethanol (Suzhou Ote Chemical Co., Ltd.) and 0.06 parts of DAPPO R DF 3163 (Deqian Company) was added into the dispersion tank, stirred at a rate of 150 rpm for 0.5 h, and then filtered to obtain the highly weather-resistant inorganic red gravure ink.

[0123] Embodiment 9 (dispersant with block copolymer structure + resin A + resin B + inorganic pigment):

[0124] Step 1: Preparation of dispersant:

[0125] (1) 3 g of the precursor, 0.2 g of azobisisocyanovaleric acid initiator, 37.84 g of MAA, and 106 g of dioxane were mixed, and after nitrogen was passed through to remove oxygen, the mixture was reacted at 80° C. for 2 hours. The structural formula of the precursor is: Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0126] (2) Add 6 g of MMA, 0.2 g of azobisisocyanovaleric acid initiator, and 32 g of dioxane, and react at 80° C. for 12 hours after nitrogen is passed through to remove oxygen;

[0127] (3) Cooling to room temperature, using cyclohexane as a precipitant to precipitate the dispersant, and vacuum drying to obtain the dispersant with n1=3 and n2=22.

[0128] Step 2: Preparation of ink:

[0129] 24 parts of resin A were added to the dispersion kettle, stirring was started, and the speed was maintained at 150 rpm. Then 12 parts of purified water, 0.03 parts of monoethanolamine (BASF), 3 parts of the above-mentioned dispersant with a block copolymer structure of n1=3, n2=22, 0.06 parts of DAPPO were added in sequence. R DF 3163 (Deqian Company) and 10 parts of iron oxide yellow 4920FM 4130 (Lanxess), and stirred and mixed at a rate of 200 rpm, and then transferred to a horizontal sand mill, ground until the color paste particle size reaches less than 300 nm, and then filtered to obtain an aqueous yellow paste; then the obtained aqueous yellow paste, 14 parts of resin B (refer to the synthesis method of Example 2), the remaining 34.06 parts of purified water in the formula, 0.8 parts of BYK-349 (BYK), 2 parts of ethanol (Suzhou Out Chemical Co., Ltd.) and 0.08 parts of DAPPO R DF 3163 (Deqian Company) was added into the dispersion tank, stirred at a rate of 250 rpm for 1 hour, and then filtered to obtain the highly weather-resistant inorganic yellow gravure printing ink.

[0130] Embodiment 10 (dispersant with random copolymer structure + resin A + resin B + inorganic pigment):

[0131] Step 1: Preparation of dispersant:

[0132] (1) 3 g of the precursor, 0.4 g of azobisisocyanovaleric acid initiator, 37.84 g of MAA, 6 g of MMA, and 138 g of dioxane were mixed, and the mixture was reacted at 80° C. for 12 hours after nitrogen was passed through the mixture to remove oxygen. The structural formula of the precursor is: Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0133] (2) Cooling to room temperature, using cyclohexane as a precipitant to precipitate the dispersant, and vacuum drying to obtain the dispersant having a random copolymer structure. Vacuum drying to obtain the dispersant having a random copolymer structure with n1=3 and n2=22.

[0134] Step 2: Preparation of ink:

[0135] 24 parts of resin A were added to the dispersion kettle, stirring was started, and the speed was maintained at 100 rpm. Then 12 parts of purified water, 0.03 parts of monoethanolamine (BASF), 3 parts of the above-mentioned dispersant with a random copolymer structure of n1=3, n2=22, 0.05 parts of DAPPO R DF 3163 (Deqian Company) and 10 copies 4130 (Lanxess), and stirred and mixed at a rate of 200 rpm, and then transferred to a horizontal sand mill, ground until the color paste particle size reached 4, and then filtered to obtain an aqueous inorganic yellow paste; then the obtained aqueous yellow paste, 14 parts of resin B (refer to the synthesis method of Example 2), the remaining 34.06 parts of purified water in the formula, 0.8 parts of BYK-349 (BYK), 2 parts of ethanol (Suzhou Out Chemical Co., Ltd.) and 0.08 parts of DAPPO R DF 3163 (Deqian Company) was added into the dispersion tank, stirred at a rate of 250 rpm for 1 hour, and then filtered to obtain inorganic yellow ink for gravure printing.

[0136] Example 11 (dispersant with block copolymer structure + resin A + resin B + inorganic pigment):

[0137] Step 1: Preparation of dispersant:

[0138] (1) 3 g of the precursor, 0.2 g of azobisisocyanovaleric acid initiator, 51.6 g of MAA, and 106 g of dioxane were mixed, and after nitrogen was passed through to remove oxygen, the mixture was reacted at 80° C. for 2 hours. The structural formula of the precursor is: Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0139] (2) Add 10 g of MMA, 0.2 g of azobisisocyanovaleric acid initiator, and 32 g of dioxane, and react at 80° C. for 12 hours after nitrogen is passed through to remove oxygen;

[0140] (3) Cooling to room temperature, using cyclohexane as a precipitant to precipitate the dispersant, and vacuum drying to obtain the dispersant having a block copolymer structure with n1=5 and n2=30.

[0141] Step 2: Preparation of ink:

[0142] 28 parts of resin A were added to the dispersion kettle, stirring was started, and the speed was maintained at 100 rpm. Then 14 parts of purified water, 0.01 parts of monoethanolamine (BASF), 3 parts of the above-mentioned dispersant with a block copolymer structure of n1=5, n2=30, 0.06 parts of DAPPO were added in sequence. R DF 3163 (Deqian Company) and 10 parts of iron oxide blue (Changzhou Fengshuo Chemical Co., Ltd.), and stirred and mixed at a speed of 200 rpm, and then transferred to a horizontal sand mill, ground until the color paste particle size reaches less than 300nm (3 passes), and then filtered to obtain an aqueous inorganic blue paste; then the obtained aqueous blue paste, 15 parts of resin B, the remaining 29.64 parts of pure water in the formula, 1.2 parts of BYK-349 (BYK Company), 4 parts of ethanol (Suzhou Out Chemical Co., Ltd.) and 0.1 parts of DAPPO R DF 3163 (Deqian Company) was added into the dispersion tank, stirred at a rate of 250 rpm for 1 hour, and then filtered to obtain the highly weather-resistant gravure printing inorganic blue ink.

[0143] Embodiment 12 (dispersant with random copolymer structure + resin A + resin B + inorganic pigment):

[0144] Step 1: Preparation of dispersant:

[0145] (1) 3 g of the precursor, 0.4 g of azobisisocyanovaleric acid initiator, 51.6 g of MAA, 10 g of MMA, and 138 g of dioxane were mixed, and the mixture was reacted at 80° C. for 12 hours after nitrogen was passed through the mixture to remove oxygen. The structural formula of the precursor is: Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0146] (2) Cooling to room temperature, using cyclohexane as a precipitant to precipitate the dispersant, and vacuum drying to obtain the dispersant having a random copolymer structure. Vacuum drying to obtain the dispersant having a random copolymer structure with n1=5 and n2=30.

[0147] Step 2: Preparation of ink:

[0148] 28 parts of resin A were added to the dispersion kettle, stirring was started, and the speed was maintained at 100 rpm. Then 14 parts of purified water, 0.01 parts of monoethanolamine (BASF), 3 parts of the above-mentioned dispersant with a random copolymer structure of n1=5, n2=30, 0.06 parts of DAPPO were added in sequence. RDF 3163 (Deqian Company) and 10 parts of iron oxide blue (Changzhou Fengshuo Chemical Co., Ltd.), and stirred and mixed at a speed of 200 rpm, and then transferred to a horizontal sand mill, ground until the color paste particle size reaches 4, and then filtered to obtain an aqueous inorganic blue paste; then the obtained aqueous blue paste, 15 parts of resin B, the remaining 29.64 parts of pure water in the formula, 1.2 parts of BYK-349 (BYK Company), 4 parts of ethanol (Suzhou Out Chemical Co., Ltd.) and 0.1 parts of DAPPO R DF 3163 (Deqian Company) was added into the dispersion tank, stirred at 250 rpm for 1 h, and then filtered to obtain inorganic blue ink for gravure printing.

[0149] Example 13 (dispersant with block copolymer structure + resin A + resin B + inorganic pigment):

[0150] Step 1: Preparation of dispersant:

[0151] (1) 3 g of the precursor, 0.2 g of azobisisocyanovaleric acid initiator, 41.28 g of MAA, and 106 g of dioxane were mixed, and after nitrogen was passed through to remove oxygen, the mixture was reacted at 80° C. for 2 hours. The structural formula of the precursor is: Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0152] (2) Add 8 g of MMA, 0.2 g of azobisisocyanovaleric acid initiator, and 32 g of dioxane, and react at 80° C. for 12 hours after nitrogen is passed through to remove oxygen;

[0153] (3) Cooling to room temperature, using cyclohexane as a precipitant to precipitate the dispersant, and vacuum drying to obtain the dispersant having a block copolymer structure with n1=4 and n2=24.

[0154] Step 2: Preparation of ink:

[0155] 22 parts of resin A were added to the dispersion kettle, stirring was started, and the speed was maintained at 100 rpm. Then 10 parts of purified water, 0.01 parts of monoethanolamine (BASF), 2 parts of the above-mentioned dispersant with a block copolymer structure of n1=4, n2=24, 0.04 parts of DAPPO were added in sequence. RDF 3163 (Deqian Company) and 10 parts of inorganic carbon black SPECIAL BLACK 4 (Degussa Company, Germany) were stirred and mixed at a speed of 200 rpm and then transferred to a horizontal sand mill. After grinding until the color paste particle size reached below 300 nm, the material was filtered out to obtain an aqueous inorganic black slurry; then the obtained aqueous black slurry, 14 parts of resin B, the remaining 24.64 parts of pure water in the formula, 1.2 parts of BYK-349 (BYK Company), 4 parts of ethanol (Suzhou Out Chemical Co., Ltd.) and 0.1 parts of DAPPO R DF 3163 (Deqian Company) was added into the dispersion tank, stirred at a rate of 250 rpm for 1 hour, and then filtered to obtain the highly weather-resistant gravure printing inorganic black ink.

[0156] Embodiment 14 (dispersant with random copolymer structure + resin A + resin B + inorganic pigment):

[0157] Step 1: Preparation of dispersant:

[0158] (1) 3 g of the precursor, 0.4 g of azobisisocyanovaleric acid initiator, 41.28 g of MAA, 8 g of MMA, and 138 g of dioxane were mixed, and the mixture was reacted at 80° C. for 12 hours after nitrogen was passed through the mixture to remove oxygen. The structural formula of the precursor is: Wherein, Z is an alkylthio group having four carbon atoms, and X is an isopropanoyl group;

[0159] (2) Cooling to room temperature, using cyclohexane as a precipitant to precipitate the dispersant, and vacuum drying to obtain the dispersant having a random copolymer structure. Vacuum drying to obtain the dispersant having a random copolymer structure with n1=4 and n2=24.

[0160] Step 2: Preparation of inorganic pigment paste:

[0161] 22 parts of resin A were added to the dispersion kettle, stirring was started, and the speed was maintained at 100 rpm. Then 10 parts of purified water, 0.01 parts of monoethanolamine (BASF), 2 parts of the above-mentioned dispersant with a random copolymer structure of n1=4, n2=24, 0.04 parts of DAPPO were added in sequence. R DF 3163 (Deqian Company) and 10 parts of inorganic carbon black SPECIAL BLACK 4 (Degussa Company, Germany) were stirred and mixed at a speed of 200 rpm and then transferred to a horizontal sand mill. After grinding until the color paste particle size reached below 300 nm, the material was filtered out to obtain an aqueous inorganic black slurry; then the obtained aqueous black slurry, 14 parts of resin B, the remaining 24.64 parts of pure water in the formula, 1.2 parts of BYK-349 (BYK Company), 4 parts of ethanol (Suzhou Out Chemical Co., Ltd.) and 0.1 parts of DAPPO RDF 3163 (Deqian Company) was added into the dispersion tank, stirred at a rate of 250 rpm for 1 h, and then filtered to obtain inorganic black ink for gravure printing.

[0162] Table 4 Performance data of each embodiment

[0163]

[0164] Note: In Table 4, if detailed precipitation occurs after the system is stored in hot storage, it means that the system cannot be used as a normal product, so adhesion, tinting strength and light fastness tests were not carried out.

[0165] From the comparative experiment of Example 5 and Example 7, it can be seen that Example 5 adopts resin B. Compared with the system of Example 7 adopting traditional resin, the initial viscosity of the ink and the viscosity after hot storage are lower, which is conducive to high-speed gravure printing, and it has obvious advantages in tinting strength and light resistance.

[0166] From the comparative experiments of Example 5 and Example 8, it can be seen that the inorganic pigment system using resin B also has obvious advantages in terms of light fastness compared with the traditional organic pigment system.

[0167] From the comparison between Example 3 and Example 1, it can be seen that, under the premise of using resin B, the block copolymer dispersant of the present invention is further used, and the dispersion, refinement and stabilization effect of the inorganic red pigment is significantly improved. Moreover, from the comparative experiments of Example 3 and Example 4, Example 5 and Example 6, Example 9 and Example 10, Example 11 and Example 12, and Example 13 and Example 14, it can be seen that whether resin B is used alone or in combination with resin A, the dispersant system with a block copolymer structure can further improve the comprehensive performance in various aspects.

[0168] From the comparative experiments of Example 3 and Example 5, and Example 4 and Example 6, it can be seen that the resin A prepared by the present invention has an obvious synergistic dispersion function for the inorganic red pigment, which is helpful to further improve the particle size refinement and thermal storage stability of the inorganic red pigment.

[0169] From the data of Examples 5, 9, 11, and 13 in Table 4, it can be seen that the inorganic ink paste ground by the dispersant has a particle size of less than 200 nm, and the prepared ink is stable in thermal storage without precipitation and stratification, and the viscosity changes very little, which proves the excellent dispersibility and stability of the dispersant for inorganic pigments. The inorganic ink prepared by the present invention has an adhesion of nearly 100%, and compared with the organic ink standard sample, the tinting power is more than 90%, which proves the good tinting power of the inorganic ink.

[0170] In summary, the inorganic ink prepared by the present invention has good storage stability, and its adhesion and tinting strength are close to the level of organic ink, while its weather resistance in high and low temperature sun resistance cycle test is far better than that of organic ink. It is expected to be used as a high weather resistance inorganic ink for gravure printing in the field of automotive interior decorative films.

Claims

1. A gravure printing ink, characterized in that: The invention comprises a pigment, a film-forming resin and a dispersant, wherein the dispersant is an emulsifier having a block copolymer structure used for synthesizing the film-forming resin; the film-forming resin is prepared by the following method: 5 parts by weight of an emulsifier having a block copolymer structure is dissolved in 100 parts by weight of pure water to form an aqueous phase, 0.2 parts by weight of sodium bicarbonate is added, and then an oil phase consisting of 14 parts by weight of methyl methacrylate and 2 parts by weight of n-butyl acrylate is poured into a reactor and stirred and mixed at a speed of 200-300 rpm; the temperature of the reactor is raised to 75° C., stirring is maintained, nitrogen is passed through and oxygen is removed for 10 minutes, 0.04 parts by weight of sodium persulfate is added, and the reaction is carried out until the monomer conversion rate reaches more than 95%; 28 parts by weight of n-butyl acrylate and 2 parts by weight of methyl methacrylate are added to continue the reaction until the monomer conversion rate reaches more than 95%; 0.08 parts by weight of sodium persulfate is added dissolving an initiator aqueous solution prepared in 4 parts by weight of pure water, and adding an oil phase monomer consisting of 12 parts by weight of methyl methacrylate and 1 part by weight of n-butyl acrylate, and continuing the reaction for 2-3 hours until the monomer conversion rate reaches more than 95%; adding a tert-butyl hydroperoxide aqueous solution, the tert-butyl hydroperoxide aqueous solution is obtained by dissolving 0.06 parts by weight of tert-butyl hydroperoxide in 0.6 parts by weight of pure water, and stirring at a temperature of 10-20 minutes, and then adding a Rongalite aqueous solution, the Rongalite aqueous solution is obtained by dissolving 0.06 parts by weight of Rongalite in 0.6 parts by weight of pure water, and stirring at a temperature of 10-20 minutes, and then cooling to room temperature, and finally filtering the material to obtain the film-forming resin; The chemical structural formula of the emulsifier having a block copolymer structure is: ; Wherein, n1 is the degree of polymerization of the methyl methacrylate monomer unit, n1=3-5; n2 is the degree of polymerization of the methacrylic acid monomer unit, n2=22-30.

2. The gravure printing ink according to claim 1, characterized in that: n1=4,n2=24.

3. The gravure printing ink according to claim 1, characterized in that: Also included is resin A, which is prepared by the following method: (1) Add 4g Emulsogen APS 100, 1.1g NE-10, and 3g n-butyl acrylate monomer to 90g pure water, stir at 800rpm and heat to 90℃, reduce the stirring speed to 300rpm, add potassium persulfate aqueous solution composed of 0.3g potassium persulfate dissolved in 4g pure water, and after the reaction system shows blue light, add 62g n-butyl acrylate monomer and 12g potassium persulfate aqueous solution dropwise, both of which are added at the same time, and the addition time is 7h; then reduce the temperature of the reaction system to 63℃, add 1.5g isopropanol, and then add 6g n-butyl acrylate monomer, 18g AC-76, 10g methyl methacrylate monomer, 0.8g isopropylbenzene hydroperoxide, 0.6g N,N-dimethyltoluidine, 2g NE-10 was stirred at 250 rpm for 2 hours to mix the monomer addition phase, and 6.4 g of sodium bicarbonate aqueous solution was added. The dropping speed of the sodium bicarbonate aqueous solution was adjusted to maintain the pH value of the reaction system at 5.5-7.

5. After the monomer addition phase and the sodium bicarbonate aqueous solution were added, the mixture was stirred at room temperature for 1.5 hours, 2.08 g of tert-butyl hydroperoxide aqueous solution was added, and the mixture was stirred at room temperature for 10 minutes. 2.08 g of Rongalite aqueous solution was added, and the mixture was stirred at room temperature for 10 minutes. Finally, the mixture was cooled to room temperature and discharged to obtain a silicone acrylic emulsion. The potassium sulfate aqueous solution is obtained by dissolving 2 g of potassium persulfate in 10 g of pure water; The sodium bicarbonate aqueous solution is obtained by dissolving 0.4 g of sodium bicarbonate in 6 g of pure water; The tert-butyl hydroperoxide aqueous solution is obtained by dissolving 0.08 g of tert-butyl hydroperoxide in 2 g of pure water; The Rongalite aqueous solution is obtained by dissolving 0.08g of Rongalite in 2g of pure water; (2) Take 50g of the above silicone acrylic emulsion, add it into a dispersion kettle, start stirring, add 30g of sodium silicate and 50g of silicon dioxide dispersion at a stirring speed of 200-300rpm, keep stirring for 0.5-1h, then filter and discharge the material to obtain the resin A; the solid content of the silicon dioxide dispersion is 30%-50%, and the silicon dioxide particle size is ≤100nm.

4. The gravure printing ink according to claim 1, characterized in that: The pigment is at least one of inorganic iron red pigment, iron oxide yellow, iron oxide blue and inorganic carbon black.

5. Use of the gravure printing ink according to claim 1 in automotive interior PVC decorative film.

Citation Information

Patent Citations

  • Emulsion binder, aqueous pigment ink for inkjet containing same, and method for producing emulsion binder

    CN103443218A

  • Antiviral skin-touch gloss oil applied to automotive interior film and preparation method of antiviral skin-touch gloss oil

    CN115353788A